With whom to merge? A tale of the Spanish banking deregulation process - Ana Lozano-Vivas; Miguel A. Meléndez-Jiménez; Antonio J. Morales (SERIEs - Journal of the Spanish Economic Association, 2011)
We propose a spatial competition model to study banks' strategic responses to the asymmetric Spanish geographic deregulation process. We find that once the geographic deregulation process finishes, inter-regional mergers between savings banks are optimal whenever the economies of scale associated to merging activities are low. If there are large gains, then there will be mergers between savings and commercial banks.
Keywords: C72; G21; G28; L13; L41; L51; 330; branch deregulation; mergers; optimal behavior; Spanish banking system; Bankenregulierung; Deregulierung; Bank; Fusion; Nichtkooperatives Spiel; Spanien